Umbilical Cord Mesenchymal Stem Cells Overexpressing Heme Oxygenase-1 Promotes Symptoms Recovery in Cystitis Rats by Alleviating Neuroinflammation - Qiongqiong Gao; Zhentao Gao; Minzhi Su; Yong Huang; Chi Zhang; Cuiping Li; Hailun Zhan; Bolong Liu; Xiangfu Zhou (Stem Cells International)
Interstitial cystitis/bladder pain syndrome (IC/BPS) seriously reduces the patient’s quality of life, yet current therapies only provide partial relief. In the spinal dorsal horn (SDH), neuroinflammation plays a pivotal role in the development of IC. Injection of human umbilical cord mesenchymal stem cells (hUMSCs) to reduce inflammation is an effective strategy, and heme oxygenase-1 (HO-1) exhibits anti-nociceptive effect in neuroinflammatory pain. This study aimed to test the therapeutic effects of hUMSCs overexpressing HO-1 on cyclophosphamide-induced cystitis rat model. Cystitis rats were transplanted with altered cells and then assessed for 3 weeks. A series of behavioral measurements would be trial including suprapubic mechanical allodynia, depressive-like behaviors, micturition frequency, and short-term memory function. Additionally, western blot, immunofluorescence staining, and ELISA kit test for anti-inflammation effect. HUMSCs were capable of being transduced to overexpress HO-1. Injection of hUMSCs overexpressing HO-1 was more effective than hUMSCs alone in alleviating behavioral symptoms in rats. Furthermore, hUMSCs overexpressing HO-1 inhibited the activation of glial and TLR4/p65/NLRP3 pathway, decreased the levels of pro-inflammatory cytokines in the SDH region. Surprisingly, it markedly increased anti-inflammatory cytokine IL-10, reduced MDA content, and protected GSH concentrations in local environment. Our results suggest that injecting hUMSCs overexpressing HO-1 intrathecally can significantly promote functional outcomes in cystitis rats by reducing neuroinflammation, at least, partly through downregulating TLR4/p65/NLRP3 signaling pathway in the SDH region. This cell therapy affords a new strategy for IC/BPS treatment.